The Performance of Single and Double Intake Designs of Propeller Flow Cooling System (PFCS). Issue 1 (June 2020) - Mahmuddin, F; Suhardi, A; Hariyanto, S; Syarifuddin,; Tasrief, M
Abstract: In order to save spaces inside a small-sized fishing boat, the high-pressure flow behind propeller is utilized instead of a special cooling pump to cool the main engine. From the previous study, the system is referred to as the Propeller Flow Cooling System (PFCS). As a continuation of the previous study, the present study conducted more experiments in order to compare the performance of a single and a double intake designs of the PVCS with the same cross-sectional area. The designs with circular and elliptical intakes shapes were measured. The experiments were also conducted at the Circulating Water Channel (CWC) facility. The main parameter which was compared in the experiment and analysis was the flow capacity produced by both designs for various propeller revolution (RPM). The experimental results showed that single intake design has a higher flow capacity than the double intake one which was caused by higher flow losses inside the pipe of single intake design mainly due to higher surface friction as well as an additional elbow joint needed in double intake design. This tendency occurred for both circular and elliptical shapes cases.